Impacct of teacher's behaviours on pupils achievement - Bendella, imene (My University, 2022)
Teaching often refers to the profession and to the academic knowledge and skills being taught, however, teaching involves more than basic education, for it is a more intimate process and relationship between two parties, teachers and students. In this study, we aim to understand and model the effects of various psychological factors on the relationship between teachers and their students. In mainly a descriptive research, we surveyed teachers' psychological state, mentality, character and personality, investigating their behaviours and their influence on the students. Using a qualitative approach, we have collected data from two tools: classroom observations and interviews. In addition, this research mainly aims at revealing how huge is the impact of the teachers on pupils and that teachers’ role involves more than just teaching about academic subjects, they teach about life, about morals and about values and beliefs. Therefore, it is very important that they are in the right mental and emotional state with the right attitude to educate and guide generations of students.
a case of middle school pupils of Mekkideche Abdelkader of Mostaganem
Keywords: teaching-learning process; psychological influence; student perceptions; behaviours; impact